Affacting Factor of Nursing Implementation in Prevention and Control of N A Socomial - Fitra Mayenti; Dilgu Meri; Asmalinda (Science Midwifery, 2021)
An indicator of the hospital quality is incidence of the nosocomial infections. Nosocomial infections are infections acquired by patients while being treated in the hospital. Therefore, it is necessary to prevent and control nosocomial infections to prevent nosocomial infections. The aim of this study was to determine the factors related to the nosocomial infections prevention and control by the nurses at RSUD Kota Dumai. The type of research was observational analytic with cross sectional approach. The population in this study was all nurses in the Hospital Installation Room Dumai City Hospital totaling 183 nurses with a sample of 125 respondents. The sampling technique was purposive sampling and the data were analyzed univariately and bivariately using computerization chi square tests. The results showed that the majority of 78.4% of the respondents have low education, the majority of 80.8% of the respondents have high motivation, the majority of 79,2% of the head room's supervision is good, and the majority 76% of the Nosocomial infections prevention is high. The results of statistical tests showed that there was a relationship between education (p value = 0 , 043), motivation (p value = 0.0 30 ), and supervision (p value = 0.0 03 ) with the prevention of nosocomial infections by the nurses in Dumai City Hospital. It was better for the RSUD Kota Dumai management team to increase the commitment in efforts to prevent a non-social infection in the hospital, especially in the inpatient installation room. Furthermore, the nurses supervision enhanced by the head room and the nursing field to increase the motivation and the performance of the nurses in the room